A checklist of mosses from Golden Hope Oil Palm Plantation and surrounding areas, Tawau, Sabah, East Malaysia - Monica Suleiman; Dunstan Polus Masundang; Benito C. Tan (Penerbit UMS, 2009)
A total of 56 taxa in 31 genera and 14 families of mosses were collected from Golden Hope Oil Palm Plantation area. This represents 9.3% of the 597 species of mosses reported for Sabah and 7.7% of the 724 species reported for Borneo. Acroporium convolutum var. horridulum is a new record for Borneo, whereas Ectropotheciella distichophylla is a new record for Sabah. The largest family is Calymperaceae with six genera and 14 species, followed by Hypnaceae with four genera and nine species. Oil palm plantation recorded 25 species of mosses in 16 genera, while its surrounding natural areas recorded 42 species in 25 genera.